Sustainable degradation of synthetic plastics: A solution to rising environmental concerns - Shah, Masirah Zahid; Quraishi, Marzuqa; Sreejith, Anushree; Pandit, Soumya; Roy, Arpita; Khandaker, Mayeen Uddin * (Elsevier, 2024)
Plastics have a significant role in various sectors of the global economy since they are widely utilized in agriculture, architecture, and construction, as well as health and consumer goods. They play a crucial role in several industries as they are utilized in the production of diverse things such as defense materials, sanitary wares, tiles, plastic bottles, artificial leather, and various other household goods. Plastics are utilized in the packaging of food items, medications, detergents, and cosmetics. The overconsumption of plastics presents a significant peril to both the ecosystem and human existence on Earth. The accumulation of plastics on land and in the sea has sparked interest in finding ways to breakdown these polymers. It is necessary to employ suitable biodegradable techniques to decrease the accumulation of plastics in the environment. To address the environmental issues related to plastics, it is crucial to have a comprehensive understanding of the interaction between microorganisms and polymers. A wide range of creatures, particularly microbes, have developed techniques to survive and break down plastics. This review specifically examines the categorization of plastics based on their thermal and biodegradable properties, as well as the many types of degradation and biodegradation. It also discusses the various types of degradable plastics, the characterization of biodegradation, and the factors that influence the process of biodegradation. The plastic breakdown and bioremediation capabilities of these microbes make them ideal for green chemistry applications aimed at removing hazardous polymers from the ecosystem.